ESCHATOLOGICAL MOTIVES IN THE SCIENCE FICTION NOVEL BY A. GOROKHOV “THE RELIANCE HERO” - Tatyana Djalalitdinovna Polatova (Galaxy International Interdisciplinary Research Journal, 2024)
The article is devoted to the study of A. A. Gorokhov’s novel “The Reluctant Hero”. The material examines the eschatological motifs identified in the novel. An analysis of the symbiosis of science fiction and Christian eschatological thought in the plot of the work is carried out.